An adaptive error concealment method selection algorithm for multi-view video coding - Lee, Pei-Jun; Kuo, Kuei-Ting (2013 IEEE International Conference on Consumer Electronics (ICCE), 2013)
This study proposes an adaptive error concealment method selection for multi-view transmission. This study uses the neighboring block motion vector of the damaged block to define two motion correlations, motion degree and homogenous degree, which are used to select the suitable error concealment method for the damaged block construction by the proposed fuzzy reasoning. The simulation results show that the proposed algorithm can select suitable error concealment algorithm for the damaged multi-view video to reduce concealing time on homogenous damaged block and to improve the reconstructed quality on non-homogenous damaged block. In the performance evaluation, the PSNR of the proposed method have 28.11 dB to 32.4 dB.